Gambaran Regulasi Emosi Pada Santri Baru Di Pondok Pesantren Mamba’ul Ushulil Hikmah Kembaran Banyumas - Reggi Dwi Indrawan; Ririn Isma Sundari; Ita Apriliyani (Corona: Jurnal Ilmu Kesehatan Umum, Psikolog, Keperawatan dan Kebidanan, 2024)
Background: Emotion regulation is an extrinsic and intrinsic process that is responsible for monitoring, evaluating, modifying emotional reactions, and intensively and specifically to achieve goals. Emotion regulation includes changes in the quality, intensity, duration and latency of emotional reactions and expressions in the process of adaptation. Objective: To understand the description of emotional regulation in new students at the Mamba'ul Uhulil Hikmah Islamic Boarding School. Research Method: The research carried out was quantitative research with a descriptive design. The approach used during the research was cross sectional. The population is new students at the Mamba'ul Ushulil Hikmah Islamic Boarding School. The number of new students at the Mamba'ul Ushulil Hikmah Islamic Boarding School in May 2023 is 54 students. The collection technique uses Total Sampling. The research instrument uses a questionnaire whose results are processed using univariate tests. Research Results: The characteristics of respondents based on gender are mostly female (55.6%). The education level of most is junior high school (66.7%). Emotional regulation in new students at the Mamba'ul Ushulil Hikmah Islamic Boarding School is mostly in the good emotional regulation category (64.8%)